Rationalizing the phenomenon of converting Hindu temples into mosques - Omer, Spahic (IIUM, KIRKHS, 2016)
In this paper, some aspects of the phenomenon of reclaiming and converting Hindu temples into mosques, following the arrival of Islam and Muslims to the Indian shores, are discussed. The underlying reasons for the phenomenon which were not only of expedient socio-economic and political, but also of profound spiritual nature, are the focus of discussion. The main thrusts of the paper revolves around the issues pertaining to the expediency of converting temples into mosques, Muslim general tolerance towards conquered peoples, converting temples into mosques as a relative and qualified trend, as well as the relationship between converting temples into mosques and the evolution of the identity of Islamic architecture. The nature of the paper is conceptual or philosophical, rather than empirical.